Inflammation in Psoriatic Arthritis: The DIETA trial – Dietetic IntervEntion in psoriaTic Arthritis. (2020) - Leite, Beatriz; Morimoto, Melissa; Gomes, Carina; Klemz, Barbara; Genaro, Patricia; Damasceno, Nagila; Szejnfeld, Vera; Pinheiro, Marcelo
Abstract: The oxidative stress has been considered one of the main aspects related to psoriatic arthritis (PsA), diabetes, hypertension, obesity, dyslipidemia and metabolic syndrome. Based in the premise that there is a close relationship between the metabolic and inflammatory domain in PsA patients, our aim was to evaluate the role of a 12-week nutritional intervention, including hypocaloric diet and antioxidant supplementation, on inflammatory markers and disease activity in patients with PsA. A total of 97 patients diagnosed with PsA (CASPAR, 2006) were included in this randomized, double-blinded placebo-controlled trial. Patients were distributed in three different groups: control (C) that received placebo (3 g of soybean oil); diet plus supplementation (DS) with hypocaloric diet plus omega 3 supplementation (3g); diet (D) with hypocaloric diet plus placebo supplementation (3 g of soybean oil). It was evaluated skin (PASI and BSA) and joint activity (DAS28-CRP, DAS28-ESR, BASDAI) and biochemical parameters, such as inflammatory markers (CRP, ESR, adiponectin, TBARs) and glucose and fat metabolism serum levels (HbA1c, fasting glucose and insulin, total cholesterol and fractions, triglycerides, AGER, oxidized- LDL, electronegative LDL (-) and anti-LDL (-) autoantibody) at baseline (T0) and after 12-week intervention (T3). Descriptive statistics are expressed as mean, standard deviation and frequency. Results were then compared using Kruskal-Wallis, ANOVA, Wilocoxon, Man-Whitney and T-Student test and multiple regressions. Level of significance was set as p < 0.05. At baseline there was an increase of inflammatory markers (CRP, ESR, TBARs, AGER, LDL modifications), decrease of anti-inflammatory (adiponectin) and high prevalence of hypercholesterolemia (41.2%) and peripheral insulin resistance (60%). Our data showed a significant correlation between electronegative LDL and PASI and a correlation between AGER and DAS28-ESR, indicating that a decrease of inflammatory parameters could be related to skin and joint improvement. However, after 12-week nutritional intervention there has no improvement of proinflammatory markers in the group. There was only a significant increase of adiponectin serum levels in all 3 groups, suggesting a benefit effect on chronic inflammation. According our results, omega 3 supplementation was not more effective to improve inflammation, oxidative stress and disease activity.